Korporasi Produksi Pendidikan: Tantangan dan Peluang dalam Meningkatkan Daya Saing Lembaga Pendidikan Islam Transformatif - Arkam, Rohmad; Sujianto, Agus Eko; Mutohar, Prim Masrokan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Islamic educational institutions need to change the old perspective with a new paradigm. One of them is with educational production corporations. A new form of organizing and managing education that integrates several aspects, namely academic, economic, social and business without losing the important meaning of education itself which is mutually beneficial and supportive. It is hoped that this paradigm will strengthen the competitiveness of transformative Islamic educational institutions. The purpose of this article is to examine the challenges and opportunities of educational production corporations in increasing the competitiveness of transformative Islamic educational institutions. This research uses library research. The data collection technique used is literature collection, namely collecting library materials related to the research object. This research uses a library research approach. The data collection technique used is literature collection. This research involves collecting data or scientific papers that are relevant to the research object from various library sources. The results of the research show that the challenge for educational institutions in increasing their competitiveness in the era of independent learning is by using the concept of educational production corporations, namely; a) demand for superior educational production and services, in line with needs, and able to compete in the global market; b) minimal human, financial and infrastructure resources in managing the education sector; c) maintaining harmony between academic, social and economic interests in the context of educational business. Production corporations in the education sector as an effort to increase the competitiveness of transformative Islamic educational institutions can be realized one way by analyzing opportunities from the superiority of this concept.